Surface Plasmon Resonance Characterization of Biodiesel - Sadrolhosseini, Amir Reza (2011)
Surface plasmon resonance (SPR) is a technique to retrieve information on optical properties of biomaterial. Essentially, SPR depends on the optical properties of metal layer and the attached dielectric to the metal layer. It was therefore used in this work as an optical sensing unit in characterizing biodiesel and blend biodiesel for finding the relation of refractive index with concentration of oil in the oil and methanol mixture. This study also includes the novel SPR sensor for detection of corrosion of biodiesel and detection of water in biodiesel and blend biodiesel. To achieve these, two computer programs were written to carry out data acquisition, simulation and analysis of experimental data. These programs are based on matrix methods which were written with matlab software for prism configuration. The fitting process was done by iteratively adjusting the pertinent parameters such as thickness, real and imaginary parts of refractive index, until the lowest sum of the squared error was obtained. By using simulation and experimental data, the effects of sensing layer thickness and variation of wavelength on SPR signals were estimated. Various wavelengths were attempted to induce surface plasmons resonance by using Kretschman scheme. The sensing metal layer was initially sputtered on high index prism in Kretschman configuration. At a fixed sensing layer thickness, the angle of resonance was found to be very sensitive to the characteristics of biodiesel in contact with the sensing gold thin film. Normal grade palm oil biodiesel (NPB) and winter grade palm oil biodiesel (WPB) were initially prepared in tranestrification with NaOH catalyst at 60ºC and 5ºC respectively. The significant difference between NPB and WPB can be found from their dispersion curves. The difference is attributed to the much higher Palmitic acid, 16:0C content in NPB than in WPB. On the other hand, the biodiesel blend was prepared by mixing of Malaysian palm oil biodiesel and Petronas diesel fuel using hand shaking method at room temperature; and the percentage of biodiesel was from 10% to 90% (B10, B20, B30, B40, B50, B60, B70, B80 and B90). A linear relation was discovered between the refractive index and the concentration of palm oil biodiesel . In the case of coconut oil biodiesel it was prepared by mixing the virgin coconut oil and methanol at 63°C. The methyl esters, which contribute in the coconut oil biodiesel, were methyl laurate, methyl myristate and methyl palmitate. The volume ratio (methanol to oil) was found to shift from 9 v/v to 0.12 v/v while the refractive index of the mixture shifted from 1.3426 to 1.4246. Thin Polypyrrole–Chitosan coated on the gold layer was also used to detect 2Zn and2Ni in aqueous solution. The curve of the resonance angle shift against ion concentration fitted well to the Langmuir model.